Science Mapping the Knowledge Base on Student Retention in Higher Education: A Bibliometric Review of Research Papers from 1914-2022 - Murat Öztürk; Mehmet Şükrü Bellibaş; Bekir S. Gür; Enes Gök (Üniversite Araştırmaları Dergisi)
In this study, we systematically review existing research on college student retention. It utilizes a total of 5277 publications indexed either in Scopus or Web of Science from 1914 to 2022. The results show that most of the research on student retention has been conducted in English-speaking countries such as the United States, Australia, the United Kingdom, and Canada. The United States produces almost two-thirds of scholarly publications worldwide. The term ‘retention’ is commonly used alongside ‘persistence,’ ‘attrition,’ ‘engagement,’ and ‘success.’ Moreover, the term higher education is associated with dropout, completion, and academic performance, as well as new methodological terms like data mining, machine learning, learning analytics, and logistic regression. Retention is also studied in fields such as nursing, engineering, and STEM. Special attention is given to community colleges due to higher dropout rates. Unlike the United States, Australia, the United Kingdom, and Canada, where higher education research on retention is extensive, countries like China and India, which have recently expanded their higher education systems, show a comparatively limited volume of research output concerning student retention.